The Influence of Good Corporate Governance Mechanism and Audit Quality on the Level of Accounting Conservatism - Mitayanti, Mitayanti; Waskito, Iman (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objective of this study is to determine whether Managerial Ownership, an Independent Board of Commissioners, a Board of Directors, an Audit Committee, and Audit Quality influence Accounting Conservatism in Manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2022. The sampling technique was purposive sampling of 37 companies that satisfied the criteria. The technique employs panel data regression analysis with the Eviews 12 software. The outcomes of the study show that partial managerial ownership and the board of directors have an impact on accounting conservatism. Meanwhile, the independent board of commissioners, audit committee, and audit quality all demonstrate that they have little impact on accounting conservatism. Simultaneously, the research findings reveal that managerial ownership, an independent board of commissioners, a board of directors, an audit committee, and audit quality all have an impact on accounting conservatism.